Planar silver nanowire, carbon nanotube and PEDOT:PSS nanocomposite transparent electrodes. Issue 2 (23rd March 2015) - Stapleton, Andrew J; Yambem, Soniya D; Johns, Ashley H; Afre, Rakesh A; Ellis, Amanda V; Shapter, Joe G; Andersson, Gunther G; Quinton, Jamie S; Burn, Paul L; Meredith, Paul; Lewis, David A
Abstract: Highly conductive, transparent and flexible planar electrodes were fabricated using interwoven silver nanowires and single-walled carbon nanotubes (AgNW:SWCNT) in a PEDOT:PSS matrix via an epoxy transfer method from a silicon template. The planar electrodes achieved a sheet resistance of 6.6 ± 0.0 Ω /□ and an average transmission of 86% between 400 and 800 nm. A high figure of merit of 367 Ω −1 is reported for the electrodes, which is much higher than that measured for indium tin oxide and reported for other AgNW composites. The AgNW:SWCNT:PEDOT:PSS electrode was used to fabricate low temperature (annealing free) devices demonstrating their potential to function with a range of organic semiconducting polymer:fullerene bulk heterojunction blend systems.